Ocular Characteristics of Patients With Bardet–Biedl Syndrome Caused by Pathogenic BBS Gene Variation in a Chinese Cohort - Meng, Xiaohong; Long, Yanling; Ren, Jiayun; Wang, Gang; Yin, Xin; Li, Shiying (Frontiers in Cell and Developmental Biology, 2021)
Bardet-Biedl syndrome (BBS; OMIM 209900) is a rare genetic disease causing damage to multiple organs and affecting patients’ quality of life in late adolescence or early adulthood. In this study, the ocular characteristics including morphology and function, were analyzed in 12 BBS patients from 10 Chinese families by molecular diagnostics. A total of five known and twelve novel variants in four BBS genes (BBS2, 58.33%; BBS4, 8.33%; BBS7, 16.67%; and BBS9, 16.67%) were identified in 10 Chinese families with BBS. All patients had typical phenotypes of retinitis pigmentosa with unrecordable or severely damaged cone and rod responses on full-field flash electroretinography (ffERG). Most of the patients showed unremarkable reactions in pattern visual evoked potential (PVEP) and multifocal electroretinography (mfERG), while their flash visual evoked potentials (FVEP) indicated display residual visual function. Changes in the fundus morphology, including color fundus photography and autofluorescence (AF) imaging, were heterogeneous and not consistent with the patients’ functional tests. Overall, our study expands the variation spectrum of the BBS gene, showing that the ocular characteristics of BBS patients are clinically highly heterogeneous, and demonstrates the usefulness of a combination of the ffERG and FVEP assessments of visual function in the advanced stage of retinopathy in BBS.